2007
DOI: 10.1016/j.nuclphysa.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino beams as a probe of the nuclear isospin and spin–isospin excitations

Abstract: We explore the possibility of performing nuclear structure studies using low energy neutrino beams. In particular, low energy beta-beams and conventional sources (muon decay-at-rest) are considered. We present results on the total charged-current as well as flux-averaged cross sections associated to electron (anti)-neutrino scattering on oxygen, iron, molybdenum and lead, as typical examples. It is shown that by using neutrinos from low energy beta-beams, information on forbidden states, in particular the spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
133
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(147 citation statements)
references
References 80 publications
13
133
1
Order By: Relevance
“…Cross-section results for 208 Pb are taken from Ref. [76]. The reliability of our calculations is justified from the comparison of the CC neutrino-nucleus cross sections with other calculations.…”
Section: Original Cross Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-section results for 208 Pb are taken from Ref. [76]. The reliability of our calculations is justified from the comparison of the CC neutrino-nucleus cross sections with other calculations.…”
Section: Original Cross Sectionsmentioning
confidence: 99%
“…In Figure 1, we compare our calculated cross sections for the reactions ν e =ν e À 56 Fe and ν e =ν e À 40 Ar with those of Refs. [76] and [77], respectively.…”
Section: Original Cross Sectionsmentioning
confidence: 99%
“…Figure 3 shows the corresponding fluxes. The broad physics potential of such a facility, currently being analyzed, covers : • neutrino-nucleus interaction and nuclear structure studies [11,13,14,20];…”
Section: Low Energy Beta-beamsmentioning
confidence: 99%
“…A comparison of the physics potential of low energy beta-beams and conventional sources is made in [14]. In [20] it is shown that interesting information on the spin-dipole as well as higher multipoles might be obtained by the vaying the γ of the ions. Instead of varying the ions one might take different parts of the fluxes at a detector [22].…”
Section: Low Energy Beta-beamsmentioning
confidence: 99%
See 1 more Smart Citation